Modern view on the role of folates in prophylaxis of perinatal problems - І. А. Жабченко (Publishing House TRILIST, 2019)
One of the vital vitamins is folic acid (FA), or vitamin B9. The biggest positive effects of FA show precisely during pregnancy. It is necessary for normal growth, tissue development and proliferation, hematopoiesis and embryogenesis; for uterus, placenta growth and erythropoiesis. There is a correlation between folate deficiency in pregnant women and the risk of birth defects, not only related to the neural tube defect, but also other defects. So, today the first place among the folate-induced defects in the fetus development is heart failure, followed by a defect of the nervous tube, limb defects and non-enlargement of the palate and upper lip, urinary system defects. Therefore, there is a question about the external FA provision in the form of drugs for pregnant. But all synthetic drugs with FA are chemical inactive compounds, which in the human body have to go through a cascade of transformations. FA is not digested due to the genes polymorphism of the folate cycle enzymes, which occurs in about half of women. Therefore an increase in the FA dose is not a solution to this problem, since the accumulation of non-metabolized biologically inactive FA form in blood will lead to blockade of active folate receptors and increase the folate deficiency. Therefore, a stable molecule of synthetic biologically active folate form based on the FA metabolite L-5-methyltetrahydrofolate (MTHF) was created, which differs by the presence of calcium ion. The substance is called "metafolin". It quickly dissolves in the body into calcium ions and L-5-MTHF, which continues to perform all important functions of folate. It has been proven in clinical trials that, regardless of the genotype and activity of the methylenetetrahydrofolate reductase in women, metafolin have a higher bioavailability and more effectively promotes increased folate levels in plasma than the same dose of FA. On this basis a fundamentally new drug Femibion Natalcare for pregnancy and lactation was created.